Cervical Radiculopathy: Open Study on Percutaneous Periradicular Foraminal Steroid Infiltration Performed under CT Control in 30 Patients - Cyteval, Catherine; Thomas, Eric; Decoux, Eric; Sarrabere, Marie-Pierre; Cottin, Alain; Blotman, Francis; Taourel, Patrice (American Journal of Neuroradiology, 2004)
BACKGROUND AND PURPOSE: Cervical radiculopathy is a common entity that can become unremitting, seriously disrupting the patient’s work and social activities. The purpose of our study was to evaluate the feasibility, tolerance, and efficacy of transforaminal periganglionic steroid infiltration under CT control.METHODS: Thirty patients with cervical radiculopathy, despite at least 1 month of appropriate medical treatment, underwent percutaneous periradicular foraminal steroid infiltration under CT control. Sixteen patients had foraminal degenerative stenosis, and 14 patients had disk herniation. The intensity of radicular pain was scored on an analogic visual scale (AVS). Pain relief was classified as excellent when the pain had diminished by 75% or more; good, by 50%–74%; fair by 25%–49%; or poor, by less than 25%. The patients were followed up at 2 weeks and at 6 months.RESULTS: No local complications occurred after the procedure. The mean AVS pain scores were 6.5 points before the procedure and 3.3 points 2 weeks after, with significant pain relief (P < .001). Pain relief was excellent in 11 patients (37%) and good in seven patients (23%). There was no rebound of pain at the 6-month follow-up. The duration of symptoms before infiltration and the intensity and cause of radiculalgia were not predictive of radicular pain relief.CONCLUSION: Intraforaminal cervical infiltration produced substantial sustained pain relief, whatever the cause of the radiculalgia. The CT approach ensures the safety of vital structures and allows the precise injection of a steroid specifically targeted to the ganglia.